2018
DOI: 10.2147/ndt.s184216
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in the risk of insomnia symptoms among patients from general hospital outpatient clinics

Abstract: BackgroundRegion-specific differences in the prevalence of insomnia symptoms in outpatient clinics in China have received little systematic study. This study was conducted preliminarily to examine region-specific differences in the risk of insomnia symptoms in Chinese outpatients.MethodIn total, 4,399 adult outpatients (urban vs rural residents: 1,768 vs 2,631) who completed three questions focusing on insomnia symptoms were included. Their sociodemographic and clinical information were collected with standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…We mostly identified studies using other types of self-reports that were not validated for grading insomnia severity. Hence, insomnia prevalence's ranging from 5 to 50% reported in those works have to be interpreted with caution (18)(19)(20)(21)(22)(23)(24)(25). An exception was the report by Jank et al who employed the ISI for analyzing insomnia in a mixed group with and without pain complaints (40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We mostly identified studies using other types of self-reports that were not validated for grading insomnia severity. Hence, insomnia prevalence's ranging from 5 to 50% reported in those works have to be interpreted with caution (18)(19)(20)(21)(22)(23)(24)(25). An exception was the report by Jank et al who employed the ISI for analyzing insomnia in a mixed group with and without pain complaints (40).…”
Section: Discussionmentioning
confidence: 99%
“…Hence insomnia is vague term describing the phenotypes of several sleep disturbances with different underlying etiologies. Different studies of non-clinical populations worldwide assessments have reported an insomnia prevalence from 5 to 50%, mostly with a predominance in females (18)(19)(20)(21)(22)(23)(24)(25). For insomnia evaluation, subjective assessment is considered the gold standard and has been recommended for the evaluation of patients with OPD (26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible reason for the low medication use might be that many older adults hesitate to see doctors for sleep problems due to the public misconception of the reduced need for sleep among older people (Rodriguez et al, 2015). Additionally, there are only few sleep clinics and inadequate training in recognizing sleep problems among clinicians in China (Dai et al, 2013; Zheng et al, 2018). Therefore, nurses and other health professionals should carefully assess sleep problems and provide effective treatments for older people.…”
Section: Discussionmentioning
confidence: 99%
“…High pressure of life accompanying living in the higher urbanized area could be related to the association between the agomelatine group in the higher urbanized area and the increased OR and RR of the usage of the sedativehypnotics. 49,50 The agomelatine group who sought medical help in the autumn was associated with a higher risk of using the sedative-hypnotics, and this might well be related to the fact that sleep disturbance could be associated with the significant shortening of exposure to sunlight in this season. 51 In addition, antidepressant treatment-emergent insomnia is a critical issue in the treatment of depression.…”
Section: Discussionmentioning
confidence: 99%